Life cycle cost (beginning) to procurement managers - Ayob, Mohd Fairullazi (2019)
Appointed as A Speaker/Trainer by Public Works Department to provide one day training/lecture to Procurement Managers from all around Malaysia under Pensijilan Ukur Bahan -Pengurus Perolehan (Tahap 3): Program Latihan Jabatan Kerja Raya Malaysia 2019.